Learners restrict their linguistic generalizations using preemption but not entrenchment: evidence from artificial language learning studies with adults and children - Samara, A; Wonnacott, E; Saxena, G; Maitreyee, R; Fazekas, J; Ambridge, B (American Psychological Association, 2023)
A central goal of research into language acquisition is explaining how, when learners generalize to new cases, they appropriately RESTRICT their generalizations (e.g., to avoid producing ungrammatical utterance such as *The clown laughed the man). The past 30 years have seen an unresolved debate between STATISTICAL PREEMPTION and ENTRENCHMENT as explanations. Under preemption, the use of a verb in a particular construction (e.g., *The clown laughed the man) is probabilistically blocked by hearing that verb other constructions WITH SIMILAR MEANINGS ONLY (e.g., The clown made the man laugh). Under entrenchment, such errors (e.g., *The clown laughed the man) are probabilistically blocked by hearing ANY utterance that includes the relevant verb (e.g., by The clown made the man laugh AND The man laughed). Across five artificial-language-learning studies, we designed a training regime such that learners received evidence for the (by the relevant hypothesis) ungrammaticality of a particular unattested verb/noun+particle combination (e.g., *chila+kem; *squeako+kem) via either preemption only or entrenchment only. Across all five studies, participants in the preemption condition (as per our preregistered prediction) rated unattested verb/noun+particle combinations as less acceptable for restricted verbs/nouns, which appeared during training, than for unrestricted, novel-at-test verbs/nouns, which did not appear during training; i.e., strong evidence for preemption. Participants in the entrenchment condition showed no evidence for such an effect (and in 3/5 experiments, positive evidence for the null). We conclude that a successful model of learning linguistic restrictions must instantiate competition between different forms only where they express the same (or similar) meanings.